The epidemiology of malaria in four districts in southern Mozambique receiving indoor residual spray as part of a cross-border initiative - Rajendra Maharaj; Nada Abdelatif; Mara Maquina; Ishen Seocharan; Vishan Lakan; Krijn Paaijmans; Francois Maartens; Pedro Aide; Francisco Sauté (Malaria Journal)
Abstract Background Imported malaria from southern Mozambique drives low levels of disease transmission in KwaZulu-Natal, South Africa. Therefore, the South African Department of Health funded implementation of indoor residual spraying (IRS) in Mozambiquan districts identified as sources of malaria infection for border communities in KwaZulu-Natal. IRS was initiated in districts of Guija, Inharrime, Panda and Zavala. To determine impact of spraying on malaria transmission in these districts, data relating to incidence and prevalence was collected before spraying (2018) and before the second round of spraying was completed (2023). Implementation of IRS was also monitored to ensure optimal spray coverage was achieved. Methods The study was a cross-sectional survey conducted in 6 sentinel sites in each of the four afore-mentioned districts, focusing on children 6 months to < 15 years from selected households. There was a baseline and an endline cross-sectional survey. Baseline prevalence took place during March–April 2022 whereas the endline surveys occurred during February–March 2023. One hundred and twenty children from each sentinel site were tested for malaria using rapid diagnostic tests. Monthly malaria cases were obtained from health facilities in each study district. Spray data was obtained from LSDI2 initiative who implemented IRS in the targeted districts. Results The study showed a definite impact of IRS on malaria prevalence in the targeted districts. Prevalence for sentinel sites in Guija district indicated that the prevalence of malaria increased slightly from baseline to endline in all sentinel sites in Guija. Overall, there was no significant change in prevalence in Zavala, from baseline to endline (p-value = 0.611). Panda’s overall malaria prevalence decreased from 19.20% to 10.82% (p-value < 0.001) whereas overall prevalence in Inharrime, decreased from 27.68% to 19.50% (p-value < 0.001). Malaria prevalence in children younger than 5 years decreased significantly in all four districts. In Panda there was a decrease in numbers of males and females being infected between surveys (p < 0.001), whereas for Inharrime the decrease was significant in females (p < 0.001). High coverage with IRS (> 95%) resulted in greater population protection. Conclusion The study revealed that IRS implementation decreased malaria prevalence in Inharrime and Panda but not in Guija and Zavala. To ensure that cross-border movement of people does not result in increased malaria transmission, targeting areas identified as source of infection in travelers is paramount to reaching elimination.